School Management Model to Improve Teacher Performance in Elementary Schools - Amat Zaki Mubarok; Riswandi; Ryzal Perdana; Hasan Hariri (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
There is a needs analysis of low teacher performance. This research aims to analyze school management models to improve elementary school teacher performance. This research is a type of Research and Development (R&D) research, development is carried out referring to Borg & Gall's theory. The population of this research is elementary school teachers. The subjects in this research were 74 teachers. Data collection tools use valid and reliable test instruments. Data analysis techniques with quantitative and qualitative analysis. The results of the validity data analysis test show that the school management model developed is valid for use. The results of calculating data on attractiveness, convenience and usefulness obtained an average value of 88.35 with very practical criteria. The effectiveness of the management model developed can be seen from the average N-Gain score with medium criteria and the t test shows there is a significant difference in teacher performance. The research conclusion is that the school management model developed is valid and practical to use and effective in improving the performance of elementary school teachers. The implications of this research are that management models can facilitate teachers in improving performance.